Alternatipathes alternata - Lima, Manuela M.; Cordeiro, Ralf T. S.; Perez, Carlos D. (Zenodo, 2019)
Alternatipathes alternata (Brook, 1889) Fig. 35 Bathypathes alternata Brook, 1889: 153, 180, 186, pl. 9; Cairns et al. , 2009: 94; Non Bathypathes alternata , Opresko, 1974: 127; Wagner et al. , 2011: 215, 218–219, fig. 1; Wagner et al. , 2012: 84; Brugler et al. , 2013: 343. p.p. Bathypathes patula , Pasternak, 1958: 181 –187; Pasternak 1964: 201; Pasternak, 1976: 47; Pasternak, 197: 157–159; Vinogradova, 1977: 362. Non Bathypathes patula Brook, 1889: 151–152, pl. 5. Type and type locality. BMNH 1890.4.9.21 (holotype): 36º9’57.6”N, 178º0’0”E, Pacific, 3749 m. Diagnosis. “Corallum monopodial, unbranched, pinnulate; pinnules bilateral and alternately arranged, and decreasing in length from the lower part of pinnulated stalk to upper part. Lower unpinnulated part of stem relatively short, 6–9 cm long. Maximum size of corallum usually less than 30 cm. Stem curved in abpolypar direction such that the pinnulated section is directed almost horizontally relative to substrate. Pinnules recurved downward, toward abpolypar side of colony, so that the pinnulated part of fully developed colonies forms a characteristic “wind sock” with distal ends of pinnules touching the seafloor. Longest pinnules about 10–12 cm in length in colonies 20–30 cm tall. Ten to eleven pinnules (total) per 3 cm; density increasing on distal part of colony. Polypar spines up to 0.06 mm, abpolypar spines 0.03 mm. Polyps 3–4 mm in transverse diameter” (Molodtsova & Opresko, 2017). Distribution. Pacific and Indian Ocean (Molodtsova & Opresko, 2017), South Atlantic, South Georgia Island (fig. 35) (Smithsonian, USNM 99488, identified by D. M. Opresko; available in <http://collections.nmnh.si.edu/ search/iz/>) and Antarctica (Smithsonian, USNM 78800, 78802, 78804, 78806, 78811, identified by D. M. Opresko; available in <http://collections.nmnh.si.edu/search/iz/>); from 2670 m to 5089 m depths (Molodtsova & Opresko, 2017). Published as part of Lima, Manuela M., Cordeiro, Ralf T. S. & Perez, Carlos D., 2019, Black Corals ...